The Evolving Role of Transcatheter Tricuspid Valve Edge-to-Edge Repair in Tricuspid Regurgitation - Peng Zhang; Binbin Liu; Xiang Chen; Bin Wang; Cuilian Dai; Yan Wang (Cardiovascular Innovations and Applications)
Growing evidence indicates that severe tricuspid regurgitation (TR) is independently associated with adverse clinical outcomes. The prognostic benefit of isolated TR surgery remains unclear, and medical therapy for decompensated right heart failure alone cannot delay disease progression. TR assessment and management have substantially evolved in recent years. Currently, minimally invasive catheter-based techniques have emerged as a feasible and effective option for TR treatment in high-risk surgical patients. Transcatheter tricuspid valve edge-to-edge repair (T-TEER) has been proposed and applied as an interventional treatment for TR, and has yielded promising preliminary results. This review provides an overview of the current state of T-TEER.